1972
DOI: 10.1063/1.1661299
|View full text |Cite
|
Sign up to set email alerts
|

Preionization Control of Streamer Propagation

Abstract: Streamer velocity is experimentally shown to vary with preionization in N2 and SF6. The velocity has been controlled over orders of magnitude by introducing pulsed preionization ahead of an already propagated streamer. The preionization is produced by pulsed uv irradiation. The pulsed electric field is uniform in the gap. Avalanche-streamer conversion times were observed which agree well with prediction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…This linear arc phenomenon has been associated with a laser-enhanced streamer propagation or channelling (Bradley andDavies 1971, Bradley 1972). Bradley performed experiments in which he has enhanced the velocity of an already propagating streamer by volume pre-ionisation from a laser focused ahead of the streamer.…”
Section: Basic Theorymentioning
confidence: 99%
“…This linear arc phenomenon has been associated with a laser-enhanced streamer propagation or channelling (Bradley andDavies 1971, Bradley 1972). Bradley performed experiments in which he has enhanced the velocity of an already propagating streamer by volume pre-ionisation from a laser focused ahead of the streamer.…”
Section: Basic Theorymentioning
confidence: 99%
“…Because the triggering spark radiation propagates in the form of a spherical wave and there are varying degrees of field enhancement at the cathode surface, the initial homogeneous discharge is observed in figure 5(a). It has been proved that pre-ionization ahead of a formed streamer can accelerate its propagation [27], which can explain why the initial discharge velocity on the cathode side (0.56 mm ns −1 ) is higher than that on the anode side (0.21 mm ns −1 ).…”
Section: Discussionmentioning
confidence: 99%
“…One probable reason is that nearby neutral molecules absorb most photons generated by the trigger gap discharge and only a few reach the cathode surface. Therefore, few initial electrons are generated at the cathode surface, and the intensity of continuous pre-ionization [27] is weakened to a great degree, which might restrain the cathode discharge. Figure 8(d) provides a breakdown model of the anode side sub-gap.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in the velocity of propagation of the streamer head with a n increase in the distance between the metallic particle and the insulator surface is associated with the role the insulator plays in the multiplication of charge carriers. It has been shown that the streamer propagation velocity is a function of the charge density a t the head of the streamer channel [21]. The velocity is found to be proportional to the cube root of the charge density a t the streamer tip [22].…”
Section: Experimental Arrangementmentioning
confidence: 99%